2007
DOI: 10.1021/bc070116l
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Polyamidoamine Dendrimers on Biodegradable Microparticles for Nonviral Gene Delivery

Abstract: We report on the preparation and characterization of poly(D, L-lactide-co-glycolide) (PLGA) microparticles with surface-conjugated polyamidoamine (PAMAM) dendrimers of varying generations. The buffering capacity and zeta-potential of the PLGA PAMAM microparticles increased with increasing generation level of the PAMAM dendrimer conjugated. Conjugation of the PAMAM dendrimer to the surface of the PLGA microparticle removed generation-dependent cytotoxicity in HEK293 and COS7 cell lines. PLGA PAMAM pDNA micropar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 46 publications
3
67
0
Order By: Relevance
“…[18,26,27] The positive charge of the PEI results in effective binding to the negatively charged plasmid DNA (pDNA), and this condensation protects the pDNA from digestion in serum and as the nanoparticle complex enters cells. [28,29] Once in the endosomal compartment, PEI can act as a buffer or "proton sponge" to induce osmotic swelling and cause release from the endosome. This is necessary to avoid degradation of the plasmid DNA when the endosome fuses with the lysosome.…”
Section: Introductionmentioning
confidence: 99%
“…[18,26,27] The positive charge of the PEI results in effective binding to the negatively charged plasmid DNA (pDNA), and this condensation protects the pDNA from digestion in serum and as the nanoparticle complex enters cells. [28,29] Once in the endosomal compartment, PEI can act as a buffer or "proton sponge" to induce osmotic swelling and cause release from the endosome. This is necessary to avoid degradation of the plasmid DNA when the endosome fuses with the lysosome.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a few studies in the literature that have reported the formulation of dendrimers into particulate carriers [36]. Most of those studies have focused on the encapsulation of G3-NH 2 -plasmid DNA complex (dendriplexes) into PLGA microparticles [36].…”
Section: Resultsmentioning
confidence: 99%
“…Most of those studies have focused on the encapsulation of G3-NH 2 -plasmid DNA complex (dendriplexes) into PLGA microparticles [36]. One of the important findings from those studies was the ability to sustain the release of these dendriplexes from the polymeric core over extended periods of time, suggesting that formulating dendrimer conjugates into polymeric matrices can be a potential strategy to further enhance their efficacy as drug delivery agents [36]. To the best of our knowledge, there have been no previous articles reporting the encapsulation of dendrimers into polymeric NPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 A positive surface charge of untargeted polyplexes was necessary for binding to the negatively charged cellular membrane, which in turn facilitated uptake into the cell. [26][27][28] Figure 5A showed that at a w/w ratio of 0.5, the particle size of PEI-Et/pDNA complexes was 379 nm, the zeta potential was 2 mV, indicating poor complexation between pDNA and PEI-Et. However, with an increase in w/w ratio from 1 to 30, PEI-Et could efficiently condense pDNA into nanoparticles with relatively constant diameters ranging from 130 nm to 180 nm, suggesting the formation of stable complexes with a size appropriate for gene delivery.…”
Section: Characterization Of Pei-et/pdna Complexesmentioning
confidence: 99%